Development and validation of primary health care quality assessment tool - Pouria Farrokhi; Ehsan Zarei; Rafat Bagherzadeh; Behrooz Irannejad; Asgar Aghaei Hashjin (BMC, 2023)
Abstract Background Assessing the quality of health services gives insights to managers about the status of services delivered by them, especially from the client's perspective. Although various tools have been developed to measure the quality of primary health care (PHC), no specific tool was found in this field in Iran. Therefore, the present study was conducted to develop and validate the quality assessment tool of PHC in Iran. Methods This methodological study was conducted in 2021. In the first step, based on a literature review, an initial questionnaire was designed, and its face validity, content validity, construct validity, and reliability were evaluated. Descriptive tests, Kolmogorov-Smirnov, exploratory factor analysis, Kaiser-Myer-Olkin (KMO), and Cronbach's alpha were performed by using SPSS 22. Results The initial questionnaire included 33 items, of which three items were removed due to inconsistency with factorization. The final questionnaire consisted of 30 items and nine dimensions: interaction, efficiency, timeliness, accuracy, consultation, tangibility, safety, accessibility, and environment. The KMO and Cronbach's alpha index values were 0.734 and 0.82, respectively, indicating acceptable reliability and validity. The developed dimensions represented about 73% of the total variance. Conclusion The designed questionnaire has relatively good validity and reliability and can be used to measure the quality of PHC and to identify weaknesses in service delivery. However, researchers should carefully examine it to enhance its applicability as a standard tool for measuring PHC quality.